DEVELOPING INTERACTIVE LISTENING LEARNING MULTIMEDIA TO SUPPORT “BAHASA INGGRIS FOR GRADE TEN” BOOK - Amal, Izzul; Ikhsanudin, Ikhsanudin; Bunau, Eusabinus (Journal of English Education Program, 2021)
This research was conducted to design Interactive Listening Learning Multimedia; an interactive multimedia as a teaching and learning media to support “Bahasa Inggris for Grade Ten” book. The research aims to determine whether the interactive listening learning multimedia as the supplementary teaching media is usable to support “Bahasa Inggris for Grade Ten” book or not. The form of this research is developmental research. The method of this research was design and development research. The researcher applied ADDIE as the procedure. In this research, the researcher only implemented three phases which are analysing, designing, and developing (ADD) because of time limitation. The interview for analysing phase was administered in SMA Muhammadiyah 1 Pontianak. The researcher created the multimedia using Powerpoint. In development phase, the researcher used internal evaluation to make sure that the multimedia is usable. To sum up, it is found that interactive listening learning multimedia is usable to support “Bahasa Inggris for Grade Ten” Book.